PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL: KEPUASAN KERJA DAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING - LINA LINA; STELLA STELLA (Jurnal Bisnis dan Akuntansi, 2013)
The effect of participative budgeting on managerial performance has been en interesting topic of research for many years. The objective of this research is to give an empirical evidence about the intervening effect of job satisfaction and job relevant information on the relationship between participative budgeting and managerial performance. Data were collected via questionnaires completed by managers drawn from a variety of functional areas in manufaturing companies. This study use the structural equation modelling. The result reveals that participative budgeting has positive influence to managerial performance, job satisfaction, and job relevant information. Job satisfaction has positive influence to managerial performance. Job relevant information has positive influence to job satisfaction but the other side has no influence to managerial performance. The result also shows that job satisfaction and job relevant information do not have intervening effect on the relationship between participative budgeting and managerial performance